Envelhecimento após deformação em fios máquina de aços perlíticos: efeito dos teores de boro e de enxofre - Getúlio Fonseca dos Santos (2018)
The occurrence of strain aging in pearlitic steels is characterized, in terms of mechanical properties, by an increase in the ultimate tensile strength, yield strength and a drop in ductility. The objective of this work was to characterize the susceptibility to strain aging in wire rods of three perlite steels, with different boron and sulfur contents, through application of tension for prestraing of 1,5 %, after aging treatment in a furnace of the type Mufle at temperatures of 100 and 175 °C for the times of 480, 900, 1800, 6000, 8100, 13320 and 14,400 s, and tensile tests. The analysis of the pearlite microstructure was performed by optical microscopy and the pearlitic interlamellar spacing was measured by atomic force microscopy. The analysis of post-treatment mechanical properties of aging was performed through the average of three samples per set in terms of variation in intensity at the yield limit, represented by parameter P, and ultimate tensile strength. The results of the characterization showed an analogous pearlite and an interlamellar spacing for the three types of steel. The results at 100 °C showed that the three types of steel presented a value between 3 % and 7 % for the parameter P and the aspect of the type of ductile fracture for the fracture surface. For the second stage, at 175 °C, the three types of steel presented maximum values of the parameter P of the order of 15 %, which was associated to the decomposition of the cementite. At this stage, the fracture surfaces investigated showed typical aspects of ductile fracture with the presence of cleavage points characteristic of the brittle fracture type. For steel with different S contents at both 100 °C and 175 °C, the ultimate tensile strength was similar, whereas for steel with B addition, higher values were found for this property. The results suggest that the element S has no influence on the intensity or duration of strain aging. As for steel with the addition of B in its composition, this element proved to be effective in decreasing the intensity of strain aging in the first stage because it is a nitride former